How do students learn German cultural values throughout podcast-mediated project-based learning AMIDST COVID-19 pandemic? - Iman Santoso (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2022)
Kulturkunde, a Germany intercultural class, pivoted to online learning due to Covid-19. Meetings switched from face-to-face to synchronous and asynchronous meetings. During these modes, students struggled learning Germany cultures throughout the podcast-mediated project-based learning. Accordingly, the paper attempts to describe how Germany-majored students learn Germany cultures during the online learning. Data were garnered from the Kulturkunde class reflection during podcast-mediated project-based learning in the state university in Yogyakarta. During these online meetings, twelve podcasts containing students’ intercultural projects were published. The findings reveal the students successfully pursued varieties of intercultural awareness. In addition, they also promote their language fluency and accuracy. To end, issues of ICT-based learning is also sought to discuss. Kulturkunde, pembelajaran budaya Jerman berubah dari tatap mukan menjadi tatap maya. Melalui kanal ini, mahasiswa berusahan keras belajar dan memahami nilai-nilai budaya Jerman secara daring melalui bantuan media podcast. Dari sini, tujuan penulisan artikel untuk mendeskripsikan bagaimana mahasiswa jurusan pendidikan bahasa Jerman berlajar budaya Jerman secara daring. Data riset diperoleh melalui kegiatan refleksi selama pembelajaran yang didokumentasikan selama pembealjaran oleh dosen di sebuah universitas negeri di Yogyakarta, Indonesia. Selama kegiatan pembealjaran daring ini, dua belas proyek podcast berhasil dipublikasikan. Hasil riset menunjukkan tidak hanya masalah perolehan nilai-nilai budaya Jerman yang diperoleh dan dipelajari, namun juga adanya kemampuan berbahasa Jerman yang meningkat. Sebagai tambahan, kemampuan pengguanaan teknologi pendidikan juga menjadi berkembang. Kata Kunci: budaya Jerman, kulturkunde, proyek kelas, Podcast